2021
DOI: 10.1136/bmjopen-2021-049505
|View full text |Cite
|
Sign up to set email alerts
|

Global access to COVID-19 vaccines: a scoping review of factors that may influence equitable access for low and middle-income countries

Abstract: ObjectiveTo identify the factors contributing to equitable access to COVID-19 vaccines for low and middle-income countries (LMIC).MethodsWe conducted a scoping review following the guidelines for Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews and a five-stage framework for scoping studies. We performed systematic searches for published peer-reviewed literature in five databases: Medline, Embase, Web of Science, Global Index Medicus and COVID-19 Evidence Epistem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 58 publications
0
65
0
5
Order By: Relevance
“…At the onset of the vaccine distribution, federal and state health officials agreed that early distribution of the vaccine should first target high-risk frontline health care workers and staff at long-term care communities. However, researchers found that these two high-priority groups were among the most reluctant to receive the COVID-19 vaccine [17]. The combination of the vaccine supply is limited, and the hesitancy of the groups who had vaccines reserved for them can cause further delays in the distribution of the vaccine.…”
Section: Discussion On Treatment Approachesmentioning
confidence: 99%
“…At the onset of the vaccine distribution, federal and state health officials agreed that early distribution of the vaccine should first target high-risk frontline health care workers and staff at long-term care communities. However, researchers found that these two high-priority groups were among the most reluctant to receive the COVID-19 vaccine [17]. The combination of the vaccine supply is limited, and the hesitancy of the groups who had vaccines reserved for them can cause further delays in the distribution of the vaccine.…”
Section: Discussion On Treatment Approachesmentioning
confidence: 99%
“…The study of the responses mounted by convalescent individuals against the virus is critical to better characterize effective naturally evolved strategies to overcome disease. The relevance of this new information is highlighted if the limited scope of prophylactic vaccination efforts in developing countries is taken in count (62). For instance, regarding the extent of longterm responses, even without segregation of individuals due to the severity of their COVID-19 symptoms, it has been shown that the majority of SARS-CoV-2 infected individuals develop serum Abs that last for several months (63)(64)(65), even beyond a year after infection (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…Una de las iniciativas más sonadas para promover las licencias voluntarias para COVAX, a su vez, se enfoca en lograr tres objetivos: acelerar rápidamente el desarrollo de vacunas para COVID-19 proporcionando respaldo financiero a una variedad de candidatos prometedores, el uso de mecanismos de financiación de "incitación y disuasión" (push and pull) para estimular la inversión en riesgo en la capacidad de fabricación y asegurar el acceso equitativo a nivel mundial (Mark Eccleston-Turner & Upton, 2021). COVAX se marcó como meta asegurar al menos dos mil millones de dosis de la vacuna COVID-19 para finales de 2021, donde más del 60% serían destinadas a 92 países de bajos ingresos (Forman, Shah, Jeurissen, Jit, & Mossialos, 2021;McAdams, et al, 2020;Peacocke, et al, 2021). A fecha de octubre de 2021 "solo se han enviado 371,1 millones de dosis… queda por ver si esta meta se alcanzará en 2022" (Krishtel & Hassan, 2021).…”
Section: Intentos De Solución Y Desafíosunclassified
“…Este último punto ha despertado críticas por no haberse distribuido las vacunas según la gravedad de la situación o la resistencia de los sistemas de salud afectados por aumentos repentinos de nuevos brotes (Asundi, et al, 2021). El hecho es que los países con un poder adquisitivo mayor han recibido más del 87% de las vacunas mientras que los países con ingresos medianos o bajos solo el 0,2% (Peacocke, et al, 2021). Además, como muchos países priorizan en su vacunación nacional frente a la internacional la meta de COVAX se ha visto obstaculizada (van de Pas, et al, 2021).…”
Section: Intentos De Solución Y Desafíosunclassified